Conceptual understanding and applicability of shared decision‐making in psychiatric care: An integrative review. Issue 4 (29th November 2020) - Gurtner, Caroline; Schols, Jos M. G. A.; Lohrmann, Christa; Halfens, Ruud J. G.; Hahn, Sabine
Accessible Summary: What is known on the subject?: Shared decision‐making is a concept originating in the medical field, and it is ideally based on a trustful relationship between the patient and the health professionals involved. Shared decision‐making shows potential to strengthen patient autonomy and encourages patients to become involved in decisions regarding their treatment. What does the paper add to existing knowledge?: A universal concept and understanding of shared decision‐making with relevance specifically to psychiatric clinical practice could not be identified in the analysed literature. Shared decision‐making refers to a process, and how and whether the patient wishes to participate in the decision‐making process should be clarified from the very beginning. On the basis of this synthesizing review, a process model for psychiatric practice was specified and illustrated to help lead health professionals, patients and other supporters through the decision‐making process. What are the implications for practice?: The process of shared decision‐making should be made visible to all persons involved, and it should be stated at the beginning that a decision must be made. Decisions regarding treatment are usually not limited to a single consultation. A collaborative approach including multiple health professionals and other supporters, such as peer workers and family members, is required. Psychiatric nurses could support patients during the process of decision‐making and provide additional information, if requested. Abstract: Introduction: Patient involvement in decisions regarding treatment has increasingly been supported in health care, and therefore, shared decision‐making (SDM), as an informative and participative approach, is promoted in the scientific literature. Aim: To review the current state of research regarding the conceptual understanding and implementation of SDM in psychiatric clinical practice. Method: An integrative review that included empirical, theoretical and conceptual research published between 1997 and 2019 was conducted. For this, five health‐related databases were searched. Results: Fourteen articles were included in the synthesis. No universal conceptual understanding of SDM regarding psychiatric care could be identified, although several articles highlighted the link with other concepts, such as autonomy and patient‐centeredness. Furthermore, four additional key themes with relevance for the successful implementation of SDM in clinical practice were determined. Discussion: SDM refers to a process and is usually not limited to a single consultation. SDM shows the potential to enhance patient‐centred and recovery‐oriented care. A collaborative approach including multiple health professionals, peer workers and family members is required. Implications for Practice: The process of SDM should be made visible for all parties involved. Nurses in particular could play a key role by collecting information regarding patient's preferences and by providing support.